2013
DOI: 10.1680/grim.12.00016
|View full text |Cite
|
Sign up to set email alerts
|

Shear strength of microfine cement grouted sands

Abstract: Unconsolidated–undrained (single and multi-stage) triaxial compression tests were conducted to evaluate the shear strength of microfine cement grouted sands. Microfine cements of three different types were obtained by pulverising ordinary cements produced in Greece. Multi-stage triaxial compression tests can be used dependably for determination of the shear strength parameters of cement grouted sands. It has been observed that the Mohr–Coulomb failure criterion represents adequately the behaviour of the groute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Zebovitz et al [7], Karol [1] and Warner [8] stated that grouting could be performed easily for materials ranging from microfine cements to fine sands. Christodoulou et al [9], Markou and Droudakis [10], Hashimoto et al [11] observed that the strength of the sands increased after microfine cement was injected. Schwarz and Krizek [12] and Avci [13] suggested that the permeability coefficients of sands decreased after injecting microfine cement.…”
Section: Introductionmentioning
confidence: 99%
“…Zebovitz et al [7], Karol [1] and Warner [8] stated that grouting could be performed easily for materials ranging from microfine cements to fine sands. Christodoulou et al [9], Markou and Droudakis [10], Hashimoto et al [11] observed that the strength of the sands increased after microfine cement was injected. Schwarz and Krizek [12] and Avci [13] suggested that the permeability coefficients of sands decreased after injecting microfine cement.…”
Section: Introductionmentioning
confidence: 99%
“…Zebovitz et al (1989), Karol (2003) and Warner (2003) stated that grouting could be performed easily for materials ranging from microfine cements to fine sands. Christodoulou et al (2009), Markou andDroudakis (2013), Hashimoto et al (2016) observed that the strength of the sands increased after microfine cement was injected. Schwarz and Krizek (1994) and Avci (2019) suggested that the permeability coefficients of sands decreased after injecting microfine cement.…”
Section: Introductionmentioning
confidence: 99%
“…Permeation grouting using sodium silicate solutions has also been widely applied for its mitigation effects on individual structures (e.g. Granata et al, 2015;Lirer et al, 2006;Tsukamoto et al, , 2007, while the use of microfine cement for grouting has also been developed and examined (Markou and Droudakis, 2013;Tunçdemir and Ergun, 2009;and others). However, with the recent advent of ultra-microfine cement, with particle diameters on the order of 1 μm (Kanazawa, 2012), it has become important to seek advancement in geo-technology for permeation grouting using such micro-scaled cement materials (Hashimoto et al, 2015).…”
Section: Introductionmentioning
confidence: 99%